2006
DOI: 10.1158/1078-0432.ccr-06-0467
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Geographic Zones of Cancer Risk with Epigenetic Biomarkers in Normal Breast Tissue

Abstract: Purpose: Genetic alterations were previously identified in normal epithelia adjacent to invasive cancers. The aim of this study was to determine DNA methylation in histologically normal tissues from multiple geographic zones adjacent to primary breast tumors. Experimental Design: First, methylation status of a 4-kb region of RASSF1A promoter was interrogated using oligonucleotide-based microarray in 144 samples (primary tumors, 47; adjacent normals, 69; reduction mammoplasty tissues, 28). Second, allelic imbal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
147
2
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 40 publications
8
147
2
1
Order By: Relevance
“…In the present study no significant differences were found for BRCA1, ATM and BARD1 immunoreactivity between normal breast from cancer-containing breasts and non-cancerous breasts. Genomic instability has been reported to be present at a higher frequency in cancer-containing breasts [19,20] and hypermethylation, which can modify gene expression, of genes involved in growth regulation has been found [18,43]. A higher frequency of hypermethylation is found in benign lesions [reviewed in 44].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study no significant differences were found for BRCA1, ATM and BARD1 immunoreactivity between normal breast from cancer-containing breasts and non-cancerous breasts. Genomic instability has been reported to be present at a higher frequency in cancer-containing breasts [19,20] and hypermethylation, which can modify gene expression, of genes involved in growth regulation has been found [18,43]. A higher frequency of hypermethylation is found in benign lesions [reviewed in 44].…”
Section: Discussionmentioning
confidence: 99%
“…The semiquantitative methylation-specific PCR (qMSP) experiment was conducted and products were quantified according to the protocol described in Yan and colleagues (22). Briefly, bisulfite-converted genomic DNAs (0.5 mg) were subject to real-time PCR (RT-PCR) with methylation-specific primers (Supplementary Table S2).…”
Section: Semiquantitative Real-time Methylation-specific Pcrmentioning
confidence: 99%
“…11,12 Importantly, Helicobacter pylori infection, a major carcinogenic factor in the stomach, was shown to potently induce aberrant DNA methylation in gastric epithelial cells. 11 In addition to gastric cancers, the presence of aberrant DNA methylation in noncancerous tissues and possible association with cancer risks have been reported for liver, 13 colon, 14 esophageal, 15 breast 16 and renal cancers. 17 Genes so far analyzed in noncancerous gastric mucosae are those methylated in gastric cancers, including tumor-suppressor genes, such as CDKN2A, MLH1, CDH1, LOX and APC, 2,11,18,19 and genes with little or no expression in normal gastric mucosae, such as FLNc, HAND1 and THBD.…”
mentioning
confidence: 99%